The Existence of the Solution and the Globally Convergent Shooting Method for a Class of Two-Point Boundary Value Problems (Journal of Computational Mathematics, 2018)
A class of two-point boundary value problems are studied. A new existence theorem of solution is constructively proved and a globally convergent shooting method for it is given.